2014
DOI: 10.1002/pbc.25093
|View full text |Cite
|
Sign up to set email alerts
|

High dose alkylator therapy for extracranial malignant rhabdoid tumors in children

Abstract: Patients with extracranial MRT have a poor prognosis. Treatment with high dose alkylator therapy followed by consolidation with high dose chemotherapy and autologous bone marrow transplant for those patients in radiographic complete remission appears to have a beneficial effect on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Preliminary analysis of regimen UH-1 does not, unfortunately, demonstrate clear improved outcome compared with historical data; however, further analyses are in process. While some authors discuss a potential role for even higher doses of alkylator therapy and/or high-dose chemotherapy for RTK and MRT, analogous to approaches drafted for AT/RT, 62,63 no formal trial has demonstrated a therapeutic advantage in the treatment of non-CNS RT, and any further intensification of therapy is challenged by the fact that current regimens already maintain a toxicity-related mortality of approximately 5%, as well as significant morbidity. 64 …”
Section: Historical Treatment and Outcomesmentioning
confidence: 99%
“…Preliminary analysis of regimen UH-1 does not, unfortunately, demonstrate clear improved outcome compared with historical data; however, further analyses are in process. While some authors discuss a potential role for even higher doses of alkylator therapy and/or high-dose chemotherapy for RTK and MRT, analogous to approaches drafted for AT/RT, 62,63 no formal trial has demonstrated a therapeutic advantage in the treatment of non-CNS RT, and any further intensification of therapy is challenged by the fact that current regimens already maintain a toxicity-related mortality of approximately 5%, as well as significant morbidity. 64 …”
Section: Historical Treatment and Outcomesmentioning
confidence: 99%
“…This report shows that the VIDE regimen has the potential to prolong the survival of patients with ERRT, even with metastatic lesions or in refractory disease. The patients with metastatic or refractory ERRTs typically survive less than 2 years, with the time to progression being within 2–5 months . Two of our patients (cases 1 and 2) had metastatic and refractory disease, with survival greater than 2 years with the VIDE regimen without myeloablative megatherapy.…”
Section: Discussionmentioning
confidence: 83%
“…While ERRT is treated with multimodal therapies according to MRTK and AT/RT treatment, there is no standard treatment. Cases 1 and 3 underscore the importance of surgical resection of the primary tumor, as does the positive correlation between surgical resection and survival indicated by numerous case series . An optimal chemotherapy regimen for ERRT remains undetermined, and data supporting the efficacy of any particular chemotherapeutic agent are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] In a study of 21 cases of the extracranial rhabdoid tumor by Venkatramani et al ., all patients with unresectable primary tumor died at the last follow-up. [ 11 ] However, even after complete resection, local recurrence is frequent. Cai et al .…”
Section: Discussionmentioning
confidence: 99%